THE ROLE OF POLICE IN PREVENTING AND COMBATING DOMESTIC VIOLENCE IN TURKEY - Kara, Huseyin; Ekici, Ahmet; Inankul, Hakan (European Scientific Journal, ESJ, 2014)
Actions and implementations continue increasingly in Turkey to stop domestic violence, while the issue preserves its place in public agenda. The Turkish National Police, who has a major role in the fight to stop domestic violence, organizes within its organization as well as with other institutions training seminars to increase awareness for its employees and for other stakeholders. The aim of this paper is to study the behavior, attitude and believes of police personnel against those who have been victim of domestic violence, identify mistakes and offer solutions. With this purpose interviews have been conducted with the administrators of Mor Catı Kadın Sıgınagı Vakfı [Purple Roof Woman Shelter Foundation] and Kadın Adayları Destekleme Dernegi- KA.DER [Women Candidates Support Association] to identify the mistakes of police in their responses to domestic violence issues. Additionally an analysis is provided of a survey conducted at Elmadag Vocational Police School with police officers that receive training to become Second Lieutenants in order to see the view of police towards domestic violence.